Some interesting foliicolous thyrotheceous ascomycetes from Kerala - T.K. ABRAHAM, V.B. HOSAGOUDAR and (Indian Phytopathology, 2002)
The following species were recorded in Kerala, India: Asterina combreti on leaves of Calycopteris floribunda (first record in India), A. hydnocarpi sp. nov. on leaves of Hydnocarpus macrocarpa, A. wrightiae on leaves of Wrightia tinctoria, Ferrarisia philippina on leaves of Ipomoea and Prillieuxina polyalthiae sp. nov. on leaves of Polyalthia longifolia.